Impact of organic agriculture on diversity and abundance of farmland birds in an arable landscape with hedges - Neumann, Dr. Helge; Bisschop-Larsen, Leif; Loges, Dr. Ralf; Taube, Prof. Dr. Friedhelm (2006)
A comparative study of breeding bird communities of organically and conventionally cultivated arable fields was carried out in northern Germany in 2005. The research was conducted on 40 pairs of fields (conventional/organic), which were selected with regard to similar field sizes and comparable boundary structures (particularly presence of hedges). Bird communities were solely dominated by the skylark Alauda arvensis L., which was the only frequent species on the tested pairs of fields. Diversity of farmland birds (number of species, Shannon-Index) was not affected by type of management. However, the abundance of skylarks (territories/10 ha) was significantly higher in organic than in conventional fields. As the study will be continued, the one-year findings will be verified with respect to changes of crops in rotations.